EMPIRICAL STUDY OF EXPORT COMPETITIVENESS OF AGRICULTURAL PRODUCTS IN ASEAN 3: REVEALED COMPARATIVE ADVANTAGE (RCA) APPROACH - Chanpitaksa Nutjaree; Alexandra Barbaso; Nofita Wulansari; M. Fahri Priambudi (UPT Penerbitan Universitas Jember)
Globalization in the economic field encourages the creation of free trade across countries, especially when the ASEAN Economic Community (MEA) is implemented. This condition poses opportunities and challenges for a country, especially a developing country. In an era of free trade increasingly lead to competitive competition between countries. Therefore, the writing of this paper aims to analyze how the export competitiveness of agricultural products in ASEAN 3, namely Indonesia, Philippines, and Thailand using Revealed Symmetric Comparative Advantage (RSCA) approach. The method of analysis in this study using descriptive analysis method to provide an image related to the competitiveness of export of agricultural products in ASEAN 3 and Relevead Comparative Advantages (RCA) Index. The Data in this paper used export of agricultural productn especially cocoa, cereals and maize in ASEAN 3 between 2001-2014 years. Based on the analysis, it is known that in facing the challenge of competition in the era of free market, the competitiveness of export of agricultural products still faces obstacles in competing in the market. This indicates the importance of policies directed to improve the competitiveness of agricultural products in a country. The role of government is very important in improving the productivity and quality of agricultural products in a country to enhance the competitiveness of exports in order to compete in the international market.